Protecting animals within and across borders : extraterritorial jurisdiction and the challenges of globalization - Blattner, Charlotte E. (New York, NY : Oxford University Press, 2019)
Extraterritorial jurisdiction stands at the juncture of international law and animal law and promises to open a path to understanding and resolving the global problems that challenge the core of animal law. As corporations have relocated and the animal industry (agriculture, medical research, entertainment, etc.) has dispersed its production facilities across the territories of multiple states, regulatory gaps and fears of a race to the bottom have become a pressing issue of global policy. 'Protecting Animals Within and Across Borders' provides enough background to allow readers to understand why extraterritorial jurisdiction must respond to these developments, counters objections that readers might raise, and describes how to improve animal law in tandem.
Also issued in print: 2019.
Includes bibliographical references and index.
Specialized.
Description based on online resource; title from home page (viewed on July 9, 2019).
Keywords: Animal welfare -- Law and legislation; Exterritoriality; Universal jurisdiction; Law and globalization; Law; Laws of specific jurisdictions & specific areas of law